Phase II Study of Hypofractionated Proton Beam Therapy for Hepatocellular Carcinoma - Kim, Tae Hyun; Park, Joong-Won; Kim, Bo Hyun; Oh, Eun Sang; Youn, Sang Hee; Moon, Sung Ho; Kim, Sang Soo; Woo, Sang Myung; Koh, Young-Hwan; Lee, Woo Jin; Kim, Dae Yong (Frontiers in Oncology, 2020)
Background: Proton beam has an excellent depth dose distribution due to its unique physical properties and thus proton beam therapy (PBT) has been tried and showed promising outcomes in hepatocellular carcinoma (HCC). The purpose of this phase II study is to evaluate the efficacy of hypofractionated proton beam therapy (PBT) in HCC. Materials and Methods: The eligibility criteria for this study were as follows: patients with HCC lesion(s) who were failed after, were difficult-to-treat with, or refused to other local treatments; tumor size and number of ≤7 cm and ≤2, respectively, and HCC lesion(s) of ≥ 2 cm from gastrointestinal organs; Child-Pugh score of ≤7; Eastern Cooperative Oncology Group performance status ≤1; and age ≥ 18 years. The prescribed dose of PBT was 70 Gy equivalent in 10 fractions. The primary endpoint was 3-year local progression-free survival (LPFS) rate. Results: Forty-five patients were prospectively enrolled, and there were 35 men and 10 women with a median age of 63 years (range, 46 – 78 years). Thirty-seven patients had recurrent and/or residual disease, and 8 patients had treatment-naïve disease. All patients received the planned treatments without treatment interruption, and ≥ grade 3 acute toxicity did not occur. The median follow-up duration was 28.5 months (range 11.2 - 56.3 months), and local progression occurred in 2 (8.7%) patients. The 3-year rates of LPFS and overall survival (OS) were 95.2% (95% confidence interval [CI], 89.1 - 100%) and 86.4% (95% CI, 72.9 – 99.9%), respectively. Conclusion: Hypofractionated PBT showed promising LPFS and OS and further studies are warranted to compare PBT with other local modalities.